2016
DOI: 10.1155/2016/9025905
|View full text |Cite
|
Sign up to set email alerts
|

Connexin’s Connection in Breast Cancer Growth and Progression

Abstract: Gap junctions are cell-to-cell junctions that are located in the basolateral surface of two adjoining cells. A gap junction channel is composed of a family of proteins called connexins. Gap junction channels maintain intercellular communication between two cells through the exchange of ions, small metabolites, and electrical signals. Gap junction channels or connexins are widespread in terms of their expression and function in maintaining the development, differentiation, and homeostasis of vertebrate tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 88 publications
(159 reference statements)
1
43
0
Order By: Relevance
“…Further studies are warranted in order to elucidate the mechanisms of GJB2 regulation in ER-negative breast tumors. It is well known that gap junctional intercellular communication (GJIC), mediated by connexins play an important role in normal mammary gland development and homeostasis, and also in the progression of breast cancer (15). In line with this, our study revealed that the knockdown of GJB2 promoted the migration and inhibited the proliferation of both breast cancer cell lines, which are ER-positive.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further studies are warranted in order to elucidate the mechanisms of GJB2 regulation in ER-negative breast tumors. It is well known that gap junctional intercellular communication (GJIC), mediated by connexins play an important role in normal mammary gland development and homeostasis, and also in the progression of breast cancer (15). In line with this, our study revealed that the knockdown of GJB2 promoted the migration and inhibited the proliferation of both breast cancer cell lines, which are ER-positive.…”
Section: Discussionsupporting
confidence: 84%
“…Connexins have been considered as tumor suppressors in many types of cancer (4)(5)(6). However, recent evidence indicates the involvement of connexins in promoting cell proliferation (7), regulating apoptosis (8), and promoting chemoresistance (9), migration (10), regulation of epithelial-mesenchymal transition (EMT) (11), tumor differentiation and angiogenesis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the lack of knowledge on its precise function and interactions in humans, it is not possible to speculate on the role of RORC in BCRL pathogenesis, preventing also any consideration of the correlation between its amplification and lymphedema occurrence. Connexins are widely expressed in the normal mammary glands, where gap junctions have distinct functions in development and homeostasis, such as modulation of cell proliferation and lactation (99). In advanced breast neoplasms, they are believed to increase the capacity of tumor cells to metastasize through enhancing their invasion and adhesion ability as well as by protecting tumor cells from hypoxia-induced death (100)(101)(102).…”
Section: Biological Characteristics Of the Primary Tumorsmentioning
confidence: 99%
“…Once there, cancer cells would thrive, using the Cx43 gap junctions to implement vital exchanges with stromal cells. 77,78 Cx43 would thus become a tumor promoter involved in the viability of metastases. In sum, weak gap junctions and connexin downregulation would be specific to proliferative and invasive cancer cells, whereas Cx43 would slow their proliferation but also promote their metastatic implantation and stromal support.…”
Section: Modulation Of Tumor Propagation By Gap Junction Intercellulamentioning
confidence: 99%